CO-DESIGNING PYTHON-BASED INTERACTIVE MEDIA FOR TRIGONOMETRY LEARNING USING CHATGPT: A PRELIMINARY STUDY - Maknun, Churun L; Rosjanuardi, Rizky; Kusumah, Yaya S (Universitas Tanjungpura, 2026)
Challenges in conceptual understanding and engagement persist in undergraduate trigonometry education, often due to static instructional methods and limited use of dynamic visual tools. Recent advances in artificial intelligence offer new opportunities for educators to independently design interactive instructional media, even without advanced programming expertise. Leveraging this potential, the present study aimed to develop and evaluate Python-based interactive media, integrating AI-generated content using the ADDIE design model. Data were collected through semi-structured interviews, Likert-scale questionnaires, and observations. Qualitative data were analysed thematically, while quantitative responses were summarised using descriptive statistics. The findings indicate that the interactive media was perceived as engaging in visualising trigonometric concepts, particularly sine and cosine, but revealed areas of confusion regarding the tangent function and challenges in self-directed learning. The study concludes that AI-assisted interactive media support conceptual understanding and student engagement, while also empowering educators to create personalised learning tools without requiring sophisticated technical skills. These results inform the design of accessible, technology-enhanced mathematics instruction